"Anything Can Happen at Any Time": Perceived Causes of Correctional Officer Injuries. (March 2022) - Goulette, Natalie; Denney, Andrew S.; Crow, Matthew S.; Ferdik, Frank V.
Prior research finds that correctional officers (COs) often report high levels of stress, poor mental and physical health and are at an increased risk of suffering work-related injuries. However, little is known about the causes of such injuries. In an attempt to fill this large gap in the literature, the current study used qualitative data to explore the perceived causes of work-related injuries according to COs and their executive staff. Officers identified the reasons for injuries as either within their control or outside of their control. Injuries resulting from factors within CO's control were perceived to be related to complacency and corruption. Injuries stemming from circumstances outside of CO's control were perceived to be related to the nature of the job, the mental health of inmates, minor events escalating, and what are known as inmate "check-ins." In consideration of these findings, policy implications and directions for future research are also reviewed.